2008
DOI: 10.1080/08916930801890280
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD5+B-1 cells in EAE pathogenesis

Abstract: Hybridoma cell lines producing natural autoantibodies (NAA), generated from A.SW mice with progressive experimental autoimmune encephalomyelitis (P-EAE), have been shown to cause demyelination and renal pathology when injected into naïve mice. To investigate the relative contribution of these antibodies to disease pathogenesis, B-1 cells, the major producers of NAA, were depleted by hypotonic shock. Depletion of B-1 cells during the effector phase of EAE significantly decreased the severity of demyelination an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
(57 reference statements)
1
21
1
Order By: Relevance
“…Depletion of the B-1 population was confirmed by flow cytometry analysis of B220, CD5, and CD19 (Figure 2). This protocol has previously been reported to reduce peritoneal B-1 cells, thereby preventing tissue injury by pathogenic natural IgM antibody (15). Lysis of the peritoneal B-1 cells did not alter overall levels of circulating IgM (Figure 2C), but it did reduce levels of mesangial IgM after sham treatment and after renal I/R compared to control mice (Figures 2D–H).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depletion of the B-1 population was confirmed by flow cytometry analysis of B220, CD5, and CD19 (Figure 2). This protocol has previously been reported to reduce peritoneal B-1 cells, thereby preventing tissue injury by pathogenic natural IgM antibody (15). Lysis of the peritoneal B-1 cells did not alter overall levels of circulating IgM (Figure 2C), but it did reduce levels of mesangial IgM after sham treatment and after renal I/R compared to control mice (Figures 2D–H).…”
Section: Resultsmentioning
confidence: 99%
“…Peritoneal B-cells were depleted as previously described (15). Mice received intraperitoneal injections of 0.5 mL of distilled water 12 days and 6 days prior to undergoing renal I/R.…”
Section: Methodsmentioning
confidence: 99%
“…Strategies that deplete peritoneal B-1a cells or that block binding of specific natural antibody clones within injured tissues have proven successful for attenuating injury in a number of different models. 23,26 We hypothesized that natural antibody IgM binds to glomerular epitopes that are exposed after adriamycin-induced injury of glomerular cells, and that bound IgM activates the complement system. To test this hypothesis, we utilized three strategies to deplete B cells in mice with adriamycin nephropathy.…”
mentioning
confidence: 99%
“…Increased levels were observed only during the late phase of remission. Previous work demonstrated that depletion of B1a B cells in mice in the induction phase of EAE development resulted in harmful effects on the incidence and clinical evolution of the pathology [42]. Thus, an association between EAE clinical evolution and B1a B cells' homeostatic maintenance could be postulated.…”
Section: Discussionmentioning
confidence: 95%